"Fact or fiction?": Oral cavity cancer in nonsmoking, nonalcohol drinking patients as a distinct entity—Scoping review. Issue 11 (27th July 2021) - Adeoye, John; Tan, Jia Yan; Ip, Cheuk Man; Choi, Siu‐Wai; Thomson, Peter
Abstract: Oral cavity cancer is often described as a lifestyle‐related malignancy due to its strong associations with habitual factors, including tobacco use, heavy alcohol consumption, and betel nut chewing. However, patients with no genetically predisposing conditions who do not indulge in these risk habits are still being encountered, albeit less commonly. The aim of this review is to summarize contemporaneous reports on these nonsmoking, nonalcohol drinking (NSND) patients. We performed database searching to identify relevant studies from January 1, 2000 to March 31, 2021. Twenty‐six articles from 20 studies were included in this study. We found that these individuals were mostly females in their eighth decade with tumors involving the tongue and gingivobuccal mucosa. This review also observed that these patients were likely diagnosed with early stage tumors with overexpression of programmed death‐ligand 1 (PD‐L1) and increased intensity of tumor infiltrating lymphocytes. Treatment response and disease‐specific prognosis were largely comparable between NSND and smoking/drinking patients.